2019
DOI: 10.1080/20008198.2019.1634938
|View full text |Cite
|
Sign up to set email alerts
|

Do adjuvant interventions improve treatment outcome in adult patients with posttraumatic stress disorder receiving trauma-focused psychotherapy? A systematic review

Abstract: Background : According to clinical guidelines, trauma-focused psychotherapies (TF-PT) such as trauma-focused cognitive behavioural therapy (TF-CBT) and eye movement desensitization and reprocessing (EMDR) are recommended as first-line treatments for posttraumatic stress disorder (PTSD). TF-CBT and EMDR are equally effective and have large effect sizes. However, many patients fail to respond or have comorbid symptoms or disorders that only partially decline with TF-PT. Thus, there is growing interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 75 publications
0
13
0
2
Order By: Relevance
“…Moreover, hydrocortisone, DCS, oxytocin, yohimbine, and methylene blue were summarized as cognitive enhancers in the previous systematic reviews. It was suggested that cortisone administration might have an adjuvant effect on PTSD symptom reduction (Michael et al, 2019). The adjuvant effect of DCS on exposure therapy was not consistent across studies but was observed on PE and VRE (Mataix‐Cols et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, hydrocortisone, DCS, oxytocin, yohimbine, and methylene blue were summarized as cognitive enhancers in the previous systematic reviews. It was suggested that cortisone administration might have an adjuvant effect on PTSD symptom reduction (Michael et al, 2019). The adjuvant effect of DCS on exposure therapy was not consistent across studies but was observed on PE and VRE (Mataix‐Cols et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…And DCS was associated with lower symptom severity than those assigned to placebo at posttreatment and at follow‐up (Mataix‐Cols et al, 2017). Michael et al (2019) reviewed the studies containing trauma‐focused therapy with adjuvant (cognitive enhancers and behaviour‐based interventions) and preliminarily found that exercise and cortisol administration might have an adjuvant effect on the PTSD symptom reduction. And there was a faster symptom reduction in the trauma‐focused CBT plus breathing biofeedback group and a trend towards an enhanced treatment effect (Michael et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anders als bei psychologischen Interventionen, bei denen oft Tage zwischen dem kritischen Ereignis und der Präventionsmaßnahme liegen, erfolgen pharmakologische Interventionen oft in einem knappen Zeitfenster von weniger als 12 Stunden (mit Ausnahme von SSRIs, die über einen längeren Zeitraum eingesetzt werden). Die angenommenen Wirkmechanismen verschiedener Substanzen sind heterogen, konzentrieren sich jedoch vor allem auf gedächtnismodulierende Effekte [9].…”
Section: Pharmakologische Interventionenunclassified
“…Clinical practice guidelines for the treatment of posttraumatic stress disorder (PTSD) strongly recommend trauma-focused cognitive behavioral therapy (TF-CBT), comprising exposure therapy as its core element (Hamblen et al, 2019). Despite TF-CBT’s effectiveness, rates of non-responders and dropouts are high (Schottenbauer et al, 2008), indicating the need for further improvements of treatment (Michael et al, 2019). Since PTSD and sleep disturbances are highly interrelated, it has been suggested that adjunctive treatments addressing sleep may enhance the efficacy of TF-CBT (Difede et al, 2014).…”
Section: Introductionmentioning
confidence: 99%